Equivalent models and mechanical properties of bio-inspired corrugated sandwich structures subjected to bending loads. (15th July 2020) - Meng, Liang; Lan, Xinqiang; Zhao, Jian; Wang, Zemin
Abstract: Corrugated sandwich structures have been widely used in aerospace and aviation fields due to their excellent performances. In this paper, a new bio-inspired corrugated sandwich structure is designed based on the microstructure of cybister elytra. Moreover, the homogenization method is used to simplify models and the equivalent material parameters are derived by analytical formulation and finite element method (FEM). The mechanical properties of bio-inspired corrugated sandwich structures fabricated by selective laser melting (SLM) and equivalent models are also investigated subjected to bending loads by FEM and experiments. The results show that the bio-inspired corrugated sandwich structure can be equivalent to the orthotropic model better. Increasing the core height, thickness of the core and panel will improve the bending stiffness obviously. The simulation results are consistent with analytical formulation. But the experimental results are little greater due to the dimension deviation between the fabrication and design. Moreover, the equivalent calculation has a much higher accuracy with a relative deviation less than 10%.